The Influence of Physical Condition Level on the Adaptive Capacity of the Organism and Stress Resistance of Students of the Faculty of Physical Education - Bielikova, Natalia; Indyka, Svitlana; Tsos, Anatolii; Sushchenko, Liudmyla; Halan-Vlashchuk, Viktor; Kotorovych, Oleksandr (My University, 2020)
Topicality. Adaptation to the higher education system is the most problematic type of adaptation. Regular physical activities cause psychological relaxation and help to withstand emotional overload. Physical сondition has a significant impact on a number of student life indicators. Determining the level of physical condition of students-athletes is the first step in substantiating the process of its improvement, and the orientation of changes in their level determines the effectiveness of the educational process at the Faculty of Physical Education. The Purpose of the Research is to identify and analyze the influence of physical condition level on the adaptive capacity of the cardiovascular system, the psycho-emotional state and the stress resistance level of physical culturist students. The Methodology of the Research. The research was conducted at the Lesya Ukrainka Eastern European National University among students of 1–4 year study on Speciality «Secondary Education. Physical Education» (135 persons, including 90 boys and 45 girls) during the intersession period. The experimental phase of the experiment took place during March-April 2018–2019. and included a study of the psycho-functional and emotional status of the research data sample. The Results the Study. It was found that adolescents are characterized by average and above average level of physical condition; the girls have high level of physical condition. A significant group of students with vegetative balance was noted; every third student has a marked vagotonia as a result of economizing the work of the human body at rest. A satisfactory level of adaptive potential was found as typical for 60 % of boys and 88,9 % for girls. It should be considered as a manifestation of long- term adaptive reaction to physical exertion. The average and high levels of the parameters «well-being» and «mood» were established; by the scale of «activity» – it was unsatisfactory for the vast majority of girls and boys. It was found 62,2 % among boys with reduced levels of stress resistance and with an average level – 36,7 % of students; among girls, 57,8 % and 40,0 %, respectively. This situation indicates the presence of stressful situations in the lives of these students and their low resistance to them. The strongest feedback was noted between the level of physical condition and heart rate and adaptive capacity.
Keywords: PE students; stress resistance; level of physical condition; adaptation potential; Vegetation Index; psycho-emotional state; 796.015.6-057.87